Implementasi IoT pada Sistem Pendeteksi Kebocoran Gas untuk Mencegah Kebakaran Rumah - Katyayana, I Gede Putu Mahasatya; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025DO - 10.24843/JNATIA.2025.v03.i03.p17, 2025)
This study aims to implement Internet of Things (IoT) technology in a LPG gas leakage detection system to prevent potential house fires. Utilizing gas sensors, Arduino, and other electronic components, this device aims to provide early warnings and quick responses to the presence of potentially hazardous gas levels. The research methodology includes system requirement analysis, device design, and functionality testing. Test results demonstrate that the system is capable of detecting leaks with good sensitivity, specifically detecting gas levels above or equal to 500. The system also accurately recognizes changes in gas concentrations and provides warnings through LED lights, Piezo alarms, and an LCD screen. Data analysis confirms the system's performance and asserts its effectiveness in emergency situations.